Influence of strain on the functionality of ink-jet printed thin films and devices on flexible substrates - Mishra, Nilesha (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2019)
Ink-jet printed devices on the flexible substrate are inexpensive and large area compatible as compared to rigid substrates. However, during fabrication and service they are subjected to complex strains, resulting in crack formation or delamination within the layers, affecting the device performance. Therefore, it is necessary to understand their failure mechanisms by correlating their electrical or structural properties with applied strain, supported by detailed microstructural investigations.